(untitled) (Research, Society and Development, 2021)
Objective: This article aims to describe the elaboration of an instagram page experience as a facilitation tool to adherence of anatomy students inside the COVID-19 pandemic. This proposal was made by second grade medical students from Faculdade de Ciências Humanas, Exatas e da Saúde do Piauí in Parnaíba-PI. Methodology: Descriptive study, experience report’s type, describing the steps of creating a sharing network for the class on social media instagram, where the sharing of images of the anatomical pieces occurred and, subsequently, the evaluation of their influence on the learning process, through a quiz. Results and discussion: The experience of managing an Instagram account as a medical student brought the possibility of developing skills such as responsibility and commitment, given the need for scientific basis, in order to avoid the spread of wrong information and, consequently, the wrong learning. Conclusion: It was observed that the approach used in the search for strategies that expand the student’s coexistence with the subjects of human anatomy was well accepted by the individuals, evidencing the high reach of the public. This contributed to the access and learning of Integrated Organic Systems applied to human anatomy, favoring the student’s familiarization with the discipline, since the contents are arranged on a platform on which they attend daily, making it possible to increase their engagement in practical laboratory classes.